2022
DOI: 10.1136/bmjophth-2021-000931
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of anterior segment optical coherence tomography in detecting plateau iris

Abstract: ObjectiveTo evaluate the diagnostic performance of manual grading of anterior segment optical coherence tomography (AS-OCT) in detection of plateau iris configuration (PIC) based on the presence of standardised ultrasound biomicroscopy (UBM) criteria in at least two quadrants; namely, clinical diagnosis of PIC (DxPIC).Methods and analysisIn this cross-sectional study, paired AS-OCT and UBM images were evaluated by three glaucoma specialists. AS-OCT was classified into two mechanisms, PIC versus non-PIC, of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Peripheral laser iridotomy is the typically first-line surgical intervention [ 8 ]. Similar to the current practice of peripheral iridotomy in primary angle closure patients, peripheral laser iridotomy of the other eye to prevent angle closure could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral laser iridotomy is the typically first-line surgical intervention [ 8 ]. Similar to the current practice of peripheral iridotomy in primary angle closure patients, peripheral laser iridotomy of the other eye to prevent angle closure could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…More cohorts are needed to validate our findings in populations with different ethnic backgrounds and those living in areas with insufficient access to medical services. Finally, the Visante AS-OCT has become outdated and been replaced by swept source AS-OCT. 33 Three-dimensional and high-resolution measurement of the anterior chamber is expected to improve our models' predictive performance.…”
Section: Limitationsmentioning
confidence: 99%
“…In one study, manual grading of AS-OCT showed poor performance in the diagnosis of PIC, and the authors suggest that it should not be used as a substitution for UBM in PIC detection among primary angle closure patients. 42 Moghimi et al . found no significant difference between anterior chamber parameters in a pupillary block and PIC patients, with plateau iris patients having a thicker peripheral iris at base.…”
Section: R Esultsmentioning
confidence: 99%